A View from Within: Lessons Learned from Partnering for Continuous Improvement. Issue 9 (September 2019) - Harrison, Christopher; Wachen, John; Brown, Stephanie; Cohen-Vogel, Lora
Background: Traditional methods of implementing educational innovations face a number of critical challenges that have problematized efforts to improve practice, particularly at scale. Recently, continuous improvement approaches have gained attention, offering structured, iterative processes for developing innovations that incorporate the wisdom of practitioners, are responsive to individual school contexts, and promote organizational learning over time. Purpose: The National Center on Scaling Up Effective Schools (NCSU) is one purveyor of such an approach, working to enact partnership-based continuous improvement processes in two large urban school districts in the U.S. This study presents a systematic, empirical investigation of the NCSU's work in order to offer recommendations for future efforts to study and implement such approaches in the complex environment of public schools. Research Design and Methods: Drawing from an analysis of over 400 hours of recorded meetings, feedback forms, and cognitive interviews with participants, this study represents a detailed case study of the NCSU's implementation of its improvement process in a large urban school district in the U.S. Conclusions: Analysis of these data reveal 3 key lessons learned by the NCSU partners. First, engaging in collaborative, partnership-based continuous improvement demands that partners construct and adopt a new culture of improvement. Second, the evolutionary nature of continuous improvement work requires partners to respond to emergent and often difficult to predict demands for new capacities and resources. Finally, efforts to implement, adapt, and expand innovations are often interwoven, competing with one another and requiring an interlocking network of supports and structures to succeed.